2014
DOI: 10.1186/s13047-014-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic foot function as a risk factor for lower limb overuse injury: a systematic review

Abstract: BackgroundDynamic foot function is considered a risk factor for lower limb overuse injuries including Achilles tendinopathy, shin pain, patellofemoral pain and stress fractures. However, no single source has systematically appraised and summarised the literature to evaluate this proposed relationship. The aim of this systematic review was to investigate dynamic foot function as a risk factor for lower limb overuse injury.MethodsA systematic search was performed using Medline, CINAHL, Embase and SportDiscus in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 89 publications
(238 reference statements)
1
36
0
Order By: Relevance
“…This means it is unclear whether differences between groups preceded the onset of injury or were a consequence of the injury. Previous systematic reviews on this topic have identified biomechanical risk factors for specific injuries (e.g., patellofemoral pain [23] or iliotibial band syndrome [24]), focused on biomechanics at one anatomic region (e.g., the foot [25]), had no specific focus on running biomechanics [25] or a running population [25], and/or included a combination of prospective and retrospective studies [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…This means it is unclear whether differences between groups preceded the onset of injury or were a consequence of the injury. Previous systematic reviews on this topic have identified biomechanical risk factors for specific injuries (e.g., patellofemoral pain [23] or iliotibial band syndrome [24]), focused on biomechanics at one anatomic region (e.g., the foot [25]), had no specific focus on running biomechanics [25] or a running population [25], and/or included a combination of prospective and retrospective studies [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…This coupling has been considered in multifactorial approaches to musculoskeletal painful conditions 3 , 4 , such as foot-ankle and knee disorders possibly related to abnormal pronation and supination 5 - 9 . Although influenced by transverse-plane motion at the knee 10 , coupling of rearfoot eversion-inversion with lower limb internal-external rotation during walking 1 , 2 may enable forces at the foot to change both rearfoot and lower limb kinematics 10 , 11 in a distal to proximal direction.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Alterations in rear-and midfoot motion are often implicated 52 as contributing factors in the cause of symptoms in these individuals. [5][6][7][8] 53…”
mentioning
confidence: 99%